IRR Incremental Analysis of Fuel Facility Construction Projects - Juanda Airport Terminal 2 - Dimas Bagus Satriyo Wibowo; Ervina Ahyudanari (IPTEK Journal of Proceedings Series, 2020)
Indonesia is the largest archipelago country in the world so that Indonesia's need for air transportation cannot be avoided. The demand for air transportation services increases in line with the increase in population and the level of welfare of the people. At Juanda Airport until the end of 2013 the number of passengers exceeds the capacity of the existing terminal. Overcoming this problem, PT Angkasa Pura I developed Terminal 2 of Juanda Airport, which began operating on 14 February 2014. With the development of facilities and flight facilities for Juanda Airport, aviation fuel supply needs have also increased. PT Pertamina (Persero) through the Aviation business unit as a provider of jet fuel at Juanda Airport, supports the development of the airport facilities. The investment carried out in 2017-2020 are the installation of a hydrant system pipeline for Terminal 2 and the addition of a storage tank to increase coverage days in the Depot Pengisian Pesawat Udara (DPPU) Juanda planned to begin in 2020. Until December 2019 the hydrant system project progress has reached 96%, but there has been a decline flight frequency since December 2018 due to partial closure of routes by airlines, reduction in flight frequencies and a decrease in jet fuel prices at market demand, so it is necessary to decide whether or not to continue investing in tank construction. Therefore, capital budgeting analysis is carried out using the incremental Internal Rate of Return (IRR) method between hydrant project investments and tank construction compared to hydrant projects without tank construction. The results of the incremental IRR analysis showed an IRR of 9.81% while the MARR used was 10.38%.